Miracle of Education The Principles and Practices of Teaching and Learning in Finnish Schools - Niemi, Hannele; Toom, Auli.; Kallioniemi, Arto.; SpringerLink (Online service) (Rotterdam : SensePublishers, 2012)
Finnish pupils$1 (Bsuccess in international student assessment tests is a hot topic everywhere in the world. The significance of Finnish educational policy and society are continuously discussed. This book provides explanations, answers and reflections to these questions. Over 30 expert authors have contributed to this book by bringing their own specific research-based viewpoints to these issues. The book describes the wholeness of the Finnish educational system, on both structural and administrative levels. It introduces the framing factors and societal conditions of education in Finland. It also explains how the Finnish educational system and teacher education function in everyday life. The book illustrates how teaching and learning of different subjects is realized in Finnish schools, and describes the essential characteristics and methods of teaching, learning materials and research on these issues. The book provides important insight and reflections to international researchers, teachers, students, journalists and policy makers, who are interested in teaching and learning in Finnish schools. It shows the results of the systematic and persistent work that has been done on education and schooling in Finland. The main features of education in Finland: - Strong equity policy - Teachers as autonomous and reflective academic experts - Flexible educational structures and local responsibility for curriculum developmentEvaluation for improvements, not for ranking - No national testing, no inspectorate - Research-based teacher education - Teachers$1 (Bhigh competence in content knowledge and pedagogy - Trust in education and teacherss
Keywords: Education; Education; Educational Policy and Politics